2009
DOI: 10.1007/s00114-009-0548-3
|View full text |Cite
|
Sign up to set email alerts
|

The response of Trissolcus basalis to footprint contact kairomones from Nezara viridula females is mediated by leaf epicuticular waxes

Abstract: Chemical footprints left behind by true bugs are perceived as contact kairomones by scelionid egg parasitoids. Female wasps encountering a contaminated artificial substrate display a characteristic arrestment posture, holding the body motionless and antennating the surface. In the system Nezara viridula (L.) and its egg parasitoid Trissolcus basalis (Wollaston), previous studies have shown that the kairomone mediating such behavior is part of N. viridula's cuticular hydrocarbons (CHC) and furthermore that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 37 publications
0
34
0
1
Order By: Relevance
“…basalis females to significantly reduce their residence time in the arena, similar to the behavior of female wasps in the presence of hexane extracts of male hosts [72]. Parasitoid response to host footprints is mediated by adsorption of the contact kairomone in the epicuticular wax layer of plants walked upon by host bugs [48,73].…”
Section: Short-range Kairomones From Nontarget Host Stagesmentioning
confidence: 69%
“…basalis females to significantly reduce their residence time in the arena, similar to the behavior of female wasps in the presence of hexane extracts of male hosts [72]. Parasitoid response to host footprints is mediated by adsorption of the contact kairomone in the epicuticular wax layer of plants walked upon by host bugs [48,73].…”
Section: Short-range Kairomones From Nontarget Host Stagesmentioning
confidence: 69%
“…This hypothesis could be extended to N. viridula females which exhibit an analogous tendency to lay egg masses far from sites where adults feed and mate (Colazza et al 1999b). Finally, O. telenomicida females do not respond to by-products of N. viridula adults, as, in open arena bioassays they were not able to detect the footprints contact chemical kairomones left by host adults walking around (Colazza et al 1999b(Colazza et al , 2009. Taking into account that O. kuvanae is attracted to volatiles produced in the accessory gland secretions of the Gypsy Moth, Lymantria dispar L. (Lepidoptera: Lymantriidae) (Hofstetter and Raffa 1998), the possibilities that O. telenomicida females can find host egg masses at short distance spying other host cues than male aggregation pheromone could not be excluded.…”
Section: Discussionmentioning
confidence: 92%
“…Different host location strategies can have strong effects in shaping extrinsic competition. The host location strategies adopted by T. basalis, have been extensively explored, showing that females are able to exploit chemical cues from adult hosts and/or injured plants in both host finding (Bin et al 1987;Mattiacci et al 1993;Colazza et al 1999bColazza et al , 2004aColazza et al , b, 2007Colazza et al , 2009Peri et al 2006;Laumann et al 2009) and host acceptance (Bin et al 1993;Mattiacci et al 1993;Aldrich et al 1995). On the contrary, no information is available on the host location strategy of O. telenomicida.…”
Section: Introductionmentioning
confidence: 97%
“…It is demonstrated that the detection of oviposition-induced synomones by the parasitoid depends on their adsorption by the epicuticular waxes. Epicuticular waxes of broad bean leaves mediated the foraging behaviour of scelionid egg parasitoid , Trissolcus basalis ( Wollaston ), by absorbing contact kairomones of the host, Nezara viridula (L.) (Colazza et al 2009 ). Wasps displayed the arrestment posture when intact leaves were contaminated by host female footprints, and it was shown earlier that disturbance of plant cuticular layer by adult insect oviposition or chemical footprints stimulate the volatile chemical production which is further used by insect's natural enemies as cues in fi nding their host's environment.…”
Section: Modifi Cation Of Plant Volatilementioning
confidence: 99%